Classification, formation, and transport mechanisms of mud clasts. Issue 12 (10th September 2017) - Li, Shunli; Li, Shengli; Shan, Xin; Gong, Chenglin; Yu, Xinghe
ABSTRACT: Mud clasts are common in non-marine to marine sedimentary records, however, why lack a widely accepted classification scheme? We propose that it is the relative balance of volumetric abundance, sorting, roundness, and grain size that controls the texture and fabric of mud clasts. Nine distinct types of mud clasts are identified in the study based on quantitatified properties, and fall into two groups coarse-grained and fine-grained. The generation of mud clasts can be assigned to failure, erosion, and/or bioturbation of muddy sediment. These clasts are transported within fluid flows including Newtonian fluids, non-Newtonian fluids, and Bingham plastics (gravity flow and turbidity flow), showing various physical characteristics depended upon the density and viscosity of flows. Newtonian flows with less density and viscosity commonly form mud clasts with mature textures. In non-Newtonian (gravity-driven) flows, mud clasts are normally transported in laminar flows with high density and viscosity, developing matrix-supported mud clasts with immature textures. The study of classification, formation, and transport mechanisms of mud clasts has implications for identifying and interpreting sedimentary environments.